Intracellular Hyper-Acidification Potentiated by Hydrogen Sulfide Mediates Invasive and Therapy Resistant Cancer Cell Death - Lee, Zheng-Wei; Teo, Xin-Yi; Song, Zhi J.; Nin, Dawn S.; Novera, Wisna; Choo, Bok A.; Dymock, Brian W.; Moore, Philip K.; Huang, Ruby Y.-J.; Deng, Lih-Wen (Frontiers in Pharmacology, 2017)
Slow and continuous release of H2S by GYY4137 has previously been demonstrated to kill cancer cells by increasing glycolysis and impairing anion exchanger and sodium/proton exchanger activity. This action is specific for cancer cells. The resulting lactate overproduction and defective pH homeostasis brings about intracellular acidification-induced cancer cell death. The present study investigated the potency of H2S released by GYY4137 against invasive and radio- as well as chemo-resistant cancers, known to be glycolytically active. We characterized and utilized cancer cell line pairs of various organ origins, based on their aggressive behaviors, and assessed their response to GYY4137. We compared glycolytic activity, via lactate production, and intracellular pH of each cancer cell line pair after exposure to H2S. Invasive and therapy resistant cancers, collectively termed aggressive cancers, are receptive to H2S-mediated cytotoxicity, albeit at a higher concentration of GYY4137 donor. While lactate production was enhanced, intracellular pH of aggressive cancers was only modestly decreased. Inherently, the magnitude of intracellular pH decrease is a key determinant for cancer cell sensitivity to H2S. We demonstrated the utility of coupling GYY4137 with either simvastatin, known to inhibit monocarboxylate transporter 4 (MCT4), or metformin, to further boost glycolysis, in bringing about cell death for aggressive cancers. Simvastatin inhibits lactate extrusion and thence contains excess lactate induced by GYY4137 within intracellular compartment. In contrast, the combined exposure to both GYY4137 and metformin overwhelms cancer cells with lactate over-production exceeding its expulsion rate. Together, GYY4137 and simvastatin or metformin synergize to induce intracellular hyper-acidification-mediated cancer cell death.